Baseline CRP Levels and Thromboembolic Events: A Retrospective Case-Control Study: CRP Levels and Thromboembolic Events - Simani, Mehrdad; Rajabi Moghaddam, Hasan; Azhdarinia, Sina; Azadchehr, Mohammad Javad; Ghaderi, Amir; Saffari, Iman (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Several studies have proposed that C-reactive protein (CRP) levels could serve as a potential indicator for predicting coronavirus disease 2019 (COVID-19); however, the findings have been inconsistent. This study aims to evaluate the relationship between baseline CRP and thromboembolic complications in patients with COVID-19. Methods: This case-control study involved two groups of COVID-19 patients admitted to Shahid Beheshti Hospital in Kashan: those with thromboembolic events (TEEs) and those without. Eligible patients were enrolled through simple random sampling based on predefined inclusion criteria. Data on patient demographics, clinical findings, and vital signs were collected using a standardized checklist. Results: We examined 70 patients with COVID-19 who experienced TEEs and 70 patients who did not. The most common underlying conditions in both groups were high blood pressure, affecting 21 individuals (30%), and diabetes, affecting 25 individuals (35.7%) (P > 0.05). In the control group, the most prevalent clinical symptoms associated with TEEs were shortness of breath, reported by 60 individuals (85.7%), and cough, reported by 46 individuals (65.7%). The incidence of shortness of breath in the case group was significantly higher than in the control group (P < 0.001). Additionally, the two groups showed significant differences in breathing rate (P = 0.002) and heart rate (P = 0.016). There was also a significant difference in CRP levels between the two groups (P = 0.038), with patients in the case group exhibiting higher CRP levels. Conclusion: This finding indicated that the level of CRP in patients with TEEs was significantly higher than in the control group. These results suggest that CRP may serve as an effective marker for identifying patients at risk of TEEs.